The Geography of Research Funding: Semantics and Beyond. (February 2020) - Skupien, Stefan; Rüffin, Nicolas
The research on cross-national research cooperation, including the categories of Global South/North, tends to leave out the issue of research funding. However, research funders are no neutral infrastructure by and for the scientific community, but represent societal, political, or economic stakeholders, whose expectations shape funding policy goals and practices. In consequence, funders need to be integrated as intermediary organization when discussing the ideology and effects of geographic pairing. In our article, we develop and sustain the proposition that an analysis of funders' views is imperative to understand the ways international research collaborations of unequally equipped participants are perceived, maintained, and sometimes reframed over time. Building on interview data and policy documents from six countries, we analyze the semantics employed to make sense of North–South relationships. We find that narratives from development cooperation complement and sometimes supersede the traditionally liberal meta-narrative of scientific collaborations.